Influence of Selected Factors on Implementation of the PPP Projects in Transport - Beata Zagożdżon; Andrzej Rogowski (Communications - Scientific letters of the University of Zilina, 2021)
Countries seek to use the knowledge and capital of the private sector to minimise the gap between the transport infrastructure needs and the capacity of their budgets. A form of private investor involvement is usually a public-private partnership PPP. However, success in implementing the PPP projects requires appropriate economic, legal and institutional conditions. The article presents results of research aimed at identifying the PPP success factors in Poland and assessing the strength of impact of individual factors on the implementation of projects. An analysis of the subject literature was carried out, based on which the success factors were determined. Next, econometric modelling methods were applied (correlation and regression), which were used to measure the degree of correlation between the variables and showed the relationships of variables to each other.